The Interaction between Ecosystem Complexity and Technological Evolution in Digital Supply Chains at Technology Companies in Indonesia - Judijanto, Loso; Sono, Moh Gifari (Westscience Press, 2025)
This study examines the interaction between ecosystem complexity and technological evolution in shaping the performance of digital supply chains at technology companies in Indonesia. Using a quantitative approach, data were collected from 115 respondents through a Likert scale-based questionnaire and analyzed using SPSS version 25. The findings reveal significant positive relationships between ecosystem complexity, technological evolution, and supply chain performance. Regression analysis highlights the critical role of ecosystem complexity in driving technological adoption, which in turn enhances supply chain efficiency and resilience. The interaction of these variables explains 62% of the variance in supply chain performance. The results underscore the importance of addressing ecosystem complexity through tailored technological solutions to maintain competitive advantage. This study provides practical implications for industry practitioners and policymakers, emphasizing the need for targeted investments in technology and infrastructure development to optimize supply chain operations in dynamic environments.